Analysis of the friction (spin) welding – preliminary study - Pietrzak Michał (MATEC Web of Conferences, 2019)
This article applies to the glue-free bonding of the components made of thermoplastics, specific techniques that use friction heat to plasticize and then join two surfaces. The featured technique is a friction (spin) welding process. Welding parameters were investigated and presented. Spin welding is known to consist of four phases. Analytical calculations were made for the first step. They are focused on the changeability of welding parameters depending on weld velocity. In the next part of this article, calculations including the finite element method were performed. This provided additional data and visualization of the process, which were not available in analytical calculations. Final results of both methods were compared. This made it possible to verify the correctness of theoretical calculations and exactness of FEM analysis.